2020
DOI: 10.3847/1538-4357/abb404
|View full text |Cite
|
Sign up to set email alerts
|

The Jet Structure and the Intrinsic Luminosity Function of Short Gamma-Ray Bursts

Abstract: The joint observation of GW170817 and GRB 170817A indicated that short gamma-ray bursts (SGRBs) can originate from binary neutron star mergers. Moreover, some SGRBs could be detected off axis, while the SGRB jets are highly structured. Then, by assuming a universal angular distribution of the jet emission for all SGRBs, we reproduce the flux and redshift distributions of the cosmological SGRBs detected by Swift and Fermi. For self-consistency, this angular distribution is simultaneously constrained by the lumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 82 publications
1
8
0
Order By: Relevance
“…90% and 50% credible intervals as functions of L log 10 and compares them to other estimations performed in other works (Ghirlanda et al 2016;Salafia et al 2020;Tan & Yu 2020). It illustrates how the short GRB luminosity function in our model peaks around L ∼ L GRB 170817A , considering this the only short GRB event observed at such a low luminosity.…”
Section: Population Studiessupporting
confidence: 81%
“…90% and 50% credible intervals as functions of L log 10 and compares them to other estimations performed in other works (Ghirlanda et al 2016;Salafia et al 2020;Tan & Yu 2020). It illustrates how the short GRB luminosity function in our model peaks around L ∼ L GRB 170817A , considering this the only short GRB event observed at such a low luminosity.…”
Section: Population Studiessupporting
confidence: 81%
“…By assuming a single-Gaussian structured jet model (e.g., Zhang & Mészáros 2002), we have shown that GW170817-like events, which can be simultaneously observed as an off-axis sGRB and a clear kilonova, may be scarce. In order to explain the sGRB signal of GW170817/GRB170817A, a two-Gaussian structured jet model may be required (Tan & Yu 2020). Future multi-messenger detection rates of sGRBs, kilonovae and afterglows can be used for constraining the jet structure.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In a statistical view, by denoting the event rate of GRBs and their luminosity function as ṘGRB and Φ(L), the detectable numbers of GRBs in different flux and redshift ranges can be calculated by [93] N…”
Section: Luminosity Functionmentioning
confidence: 99%
“…As usual, without considering the jet structure, the luminosity function is found to have a broken-power-law form. However, when a Gaussian jet structure is invoked, it can be found that a single-power-law luminosity function would become a better choice [93]. This hints that the usual low-energy power law in the luminosity function could be a result of off-axis observations.…”
Section: Luminosity Functionmentioning
confidence: 99%